2010
DOI: 10.1128/mcb.00285-10
|View full text |Cite
|
Sign up to set email alerts
|

Replication Factor C Recruits DNA Polymerase δ to Sites of Nucleotide Excision Repair but Is Not Required for PCNA Recruitment

Abstract: Nucleotide excision repair (NER) operates through coordinated assembly of repair factors into pre-and postincision complexes. The postincision step of NER includes gap-filling DNA synthesis and ligation. However, the exact composition of this NER-associated DNA synthesis complex in vivo and the dynamic interactions of the factors involved are not well understood. Using immunofluorescence, chromatin immunoprecipitation, and live-cell protein dynamic studies, we show that replication factor C (RFC) is implicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 48 publications
2
51
1
Order By: Relevance
“…Furthermore, using an assay that directly measured removal of preincorporated, radiolabeled thymine residues from acid-precipitable DNA, it was similarly reported that removal of pyrimidine dimers was nearly completely prevented by aphidicolin or HU/AraC treatment (29,55). More recently, through the use of immunofluorescence microscopy to monitor (6-4)PP content in genomic DNA, it was reported that HU/AraC treatment inhibited (37) or slowed (36,38) the rate of (6-4)PP removal. The variations in the absolute excision repair rates in these studies are likely due to differences in the cell lines, culture conditions, and proliferation states, all of which can affect dNTP levels and UV-induced DNA synthesis in quiescent cells (35,55,61,62).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, using an assay that directly measured removal of preincorporated, radiolabeled thymine residues from acid-precipitable DNA, it was similarly reported that removal of pyrimidine dimers was nearly completely prevented by aphidicolin or HU/AraC treatment (29,55). More recently, through the use of immunofluorescence microscopy to monitor (6-4)PP content in genomic DNA, it was reported that HU/AraC treatment inhibited (37) or slowed (36,38) the rate of (6-4)PP removal. The variations in the absolute excision repair rates in these studies are likely due to differences in the cell lines, culture conditions, and proliferation states, all of which can affect dNTP levels and UV-induced DNA synthesis in quiescent cells (35,55,61,62).…”
Section: Discussionmentioning
confidence: 99%
“…In a mammalian cell, this process occurs 20 -50 million times during every cell cycle (23). Pol ␦ also participates in DNA repair as a gap-filling polymerase, including nucleotide excision repair, mismatch repair, and base excision repair (70,(83)(84)(85)(86)(87)(88). ATR and ATR orthologues in yeast may stabilize replication forks that have stalled as the result of DNA polymerase inhibition (13)(14)(15)17).…”
Section: Discussionmentioning
confidence: 99%
“…26 However, it is noted that chromatin binding of PCNA to DNA repair sites can be mediated also by other factors like XPG and RPA independently of RFC and prior to the subsequent clamp loading process. 27 Thus, the accumulation of PCNA could include two or more binding steps with different kinetics that are not resolved in our experiments. The mechanistic conclusions from our work are depicted in the scheme shown in Figure 5 , two components appear in the FCS curves.…”
Section: A Model For Iswi Remodelermentioning
confidence: 99%